One-year mortality rate of patients operated for hip fracture during COVID-19 pandemic compared to pre-COVID-19 period (Annals of Medical Research, 2022)
Aim: This study aims to investigate the effects of the COVID-19 pandemic on the outcomes of patients operated for hip fractures, to determine the effect on mortality in the first postoperative year, and to compare it with the pre-pandemic period.Materials and Methods: This retrospectively designed study includes 291 patients who are operated on for hip fractures. The patients are divided into two groups: 134 patients admitted between 11 March-31 December 2019 (pre-COVID-19 period) and 157 patients admitted between 11 March-31 December 2020 (COVID-19 period). Age, gender, fracture type, an implant used, smoking habits, operation waiting time, postoperative intensive care hospitalization, length of hospital stay, COVID-19 status, Charlson comorbidity index scores, and mortality rates are evaluated based on the data from hospital the records.Results: Although there has been an increase in mortality rates in the COVID-19 period, both in the postoperative one-year one year and in the postoperative 30-day period, there is no statistically significant difference (p>0.05). Although the mortality rate of COVID-19 positive patients is higher in one-year postoperativetively than negative patients, it is demonstrated that this difference is not statistically significant (p>0.05). In addition, it is determined that the mortality rates of COVID-19 positive patients in the postoperative 30-day period has increased significantly compared to COVID-19 negatives (p=0.035). Conclusion: Mortality rates similar to those before the COVID-19 period are found  considering the one-year mortality rates in patients operated for hip fracture. However, there is a strong correlation between COVID-19 positivity and high mortality outcomes, especially in the postoperative 30-day period.